Beware the inhaled steroids or corticophobia? (Swiss Medical Weekly, 2021)
Inhaled corticosteroids have been the cornerstone of atopic, allergic asthma management for more than half a century. They have side effects (as does every medication), but they have transformed the control of asthma and saved many lives since their introduction. The current review revisits local and systemic side effects of inhaled corticosteroids and explores the prevalence and nature of parental fears (“corticophobia”) in different parts of the world. The empathetic physician treating asthma should bear in mind the impact of parental concerns on the management of this potentially life-threatening disease and try to dispel myths at every opportunity by emphasising the well-established benefits and excellent safety profile of inhaled corticosteroids.